Adaptive Boundary Observer Design for coupled ODEs-Hyperbolic PDEs systems⁎This work was sponsored within the ITEA3 European project, 15016 EMPHYSIS (Embedded systems with physical models in the production code software). Issue 2 (2020) - Ghousein, Mohammad; Witrant, Emmanuel
Abstract: We consider the state estimation of ηξ hyperbolic PDEs coupled with ηX ordinary differential equations at the boundary. The hyperbolic system is linear and propagates in the positive x-axis direction. The ODE system is linear time varying (LTV) and includes a set of ηθ unknown constant parameters, which are to be estimated simultaneously with the PDE and the ODE states using boundary sensing. We design a Luenberger state observer, and our method is mainly based on the decoupling of the PDE estimation error states from that of the ODEs via swapping design. We then derive the observer gains through the Lyapunov analysis of the decoupled system. Furthermore, we give sufficient conditions of the exponential convergence of the adaptive observer through differential Lyapunov inequalities (DLIs) and we illustrate the theoretical results by numerical simulations.